Sex Ed Experiences of Pupils. Toward Literacy in Sex Education - Giniotaitė, Akvilė (Acta Paedagogica Vilnensia, 2020)
Learning about sexuality relates to each individual learner’s identity, as everyone’s experience of sex is authentic. It is naive to attempt to force sex education on pupils and see them as tabulae rasae. Unsatisfied sexual (informational) curiosity creates circumstances wherein it is easy to fall into traditional gender roles with no ability to assess them critically, furthermore not having a set of skills to see oneself and others in a non-stereotyped manner. Young people who do not have strong, positive relationships either at home or at school face the highest possibility of participating in sexually risky behavior. Improving sexual literacy through sex education has an element of interdisciplinarity, as it includes media literacy, critical thinking, ethics, human rights, culture studies, history etc. Educational sciences become a hub that connects these different disciplines so as to ensure that the process of sex education is present and it is able to develop sexual literacy.